The effect of aspirin on arterial hypertension during pregnancy - محمد باسل; يوسف أحمد حسن; سوسي هبة (Latakia University Journal -Medical Sciences Series, 2022)
Background: Hypertensive disorders is one of the most common pregnancy problems. Over the past decades, increased attention has been paid to the use of aspirin during pregnancy and it is currently considered the most widely used treatment in the prevention of cardiovascular complications. However, the indications for the use of aspirin during pregnancy are highly controversial. Patients and methods: Study type: a retrospective comparative study. Research objective: To study the effect of daily low-dose aspirin in preventing the development of arterial hypertension during pregnancy and the occurrence of preeclampsia and its complications. The study included 110 pregnant patients who suffer from various hypertensive disorders at any gestational age who attended Tishreen University Hospital in Lattakia since its opening until July 10, 2021. They were divided into two groups, a group that was given prescription antihypertensive medication with daily low-dose aspirin after week 12 of pregnancy and a group that was given only prescription antihypertensive medication without aspirin. Vital signs were taken, laboratory tests were performed, and fetal ultrasound was evaluated. Results: Systolic and diastolic pressures were slightly higher in the group that did not take aspirin, but without statistically significant differences. We noticed that there were statistically significant differences between the two research groups regarding the presence of proteinuria, which was high in the group that did not take aspirin by 87.1% It was found that there were statistically significant differences with regard to hypertensive disorders during pregnancy, as we found that the rate of preeclampsia was high in the group that did not take aspirin by 87.1% of the group and it was in 24.2% of them with severe features, while the group that took aspirin 40% of them had preeclampsia and it was all without severe features. Conclusion: Low-dose aspirin is effective in preventing preeclampsia and its complications, so we recommend giving it at a dose of 81 mg daily after the 12th week of pregnancy and continuing it until delivery in all women with a high risk of developing preeclampsia.